Pengamatan Testing Sistem Informasi Pada Website DemoBlaze - Arly, Yehezkiel; Salim, Alissa; Rusdiansyah, Rusdiansyah (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This project aims to test a dummy e-commerce website to ensure it meets the requirements and functions properly as expected. The testing is conducted using the Python programming language with IntelliJ IDEA as the Integrated Development Environment, and utilizing a tool called Selenium to test the website with Chrome WebDriver as the connector to execute commands on the Google Chrome browser. The testing process includes simulating various user activities such as registration, login, adding items to the cart on the website, and online payment transactions. Each testing step is designed to identify and fix potential issues, ensuring that all main website functions run smoothly and meet user expectations. Furthermore, this testing aims to evaluate students' ability to write effective testing scripts. By conducting this testing, students are expected to gain valuable practical experience in software testing and enhance their understanding of the importance of testing in the software development cycle. The results of this testing are expected to enhance students' understanding of the importance of testing in the software development cycle and ensure that the e-commerce site can provide an optimal user experience. Overall, this project emphasizes the importance of comprehensive and structured testing to seek high-quality software.